Growth of Bacteria on 3-Nitropropionic Acid as a Sole Source of Carbon, Nitrogen, and Energy - Nishino, Shirley F. (American Society for Microbiology (ASM), 2010)
3-Nitropropionic acid (3NPA) is a widespread nitroaliphatic toxin found in a variety of legumes and fungi. Several enzymes have been reported that can transform the compound, but none led to the mineralization of 3NPA. We report here the isolation of bacteria that grow on 3NPA and its anion, propionate-3-nitronate (P3N), as the sole source of carbon, nitrogen, and energy. Experiments with resting cells, cell extracts, and purified enzymes indicate that the pathway involves conversion of 3NPA to P3N, which upon denitration yields malonic semialdehyde, nitrate, nitrite, and traces of H(2)O(2). Malonic semialdehyde is decarboxylated to acetyl coenzyme A. The gene that encodes the enzyme responsible for the denitration of P3N was cloned and expressed, and the enzyme was purified. Stoichiometry of the reaction indicates that the enzyme is a monooxygenase. The gene sequence is related to a large group of genes annotated as 2-nitropropane dioxygenases, but the P3N monooxygenase and closely related enzymes form a cluster within COG2070 that differs from previously characterized 2-nitropropane dioxygenases by their substrate specificities and reaction products. The results suggest that the P3N monooxygenases enable bacteria to exploit 3NPA in natural habitats as a growth substrate.